A playful attitude: Fun and seriousness in the art of the virtual worlds: How fun and seriousness in the art of the virtual worlds can predict the shape of the forthcoming future. Issue 2 (31st August 2011) - Gerosa, Mario
At the beginning of the twenty-first century, art is at a turn. In this crucial period of social changes and economical crisis, within which different generations coexist and sometimes collide, there seem to be two main directions for art and creativity. While some are persuaded that we are in a strong technological era and that art is forced to follow that trend, adapting itself to the principles and to the aesthetics of a brand-new machine age, others think that despite all the appearances, we are experimenting with a new humanism, some sort of a 'Virtual Renaissance', where the accent is not on the beauty of speed and the aesthetics of the machine as Marinetti showed us in the Futurist Manifesto (1909), where he says that a car running at full speed is better than the Nike of Samothrace, but rather this accent appears to be on the adaptation of formal values inherited from the great tradition of classical art into novel technologies. Due to this shift in perception, two behaviours seem to take shape: the first is related to a serious idea of the future, moulded on examples taken from the imaginative world of films like Cube (Natali, 1997) or The Matrix (Wachowski, 1999). The second is a softer vision of the future, without too much hiatus, a smoother change of time in contrast to the high-tech model. The ones who believe in this sweeter kind of future mock the ones who take themselves too seriously and they purposefully stress a playful attitude. They not only want to affirm that they belong to a romantic generation (the one of the baby boomers, who are situated between the old and the new), but they also mock the ones who defend an ineluctable idea of the future. This attitude is evident in many artistic expressions – with all the differences between grass roots and mainstream cultures – and it is even stronger in virtual worlds, where other important aspects also emerge. The idea of an online reputation, related to the status of the avatar, who, through his/her very embodiment, is the primary form of art in a synthetic universe is an apt example, presenting a virtual counterpart of the artist behind the keyboard, who can easily slide towards ridiculousness and nonsense if he/she embraces the cause of the playful attitude. Another aspect concerns unwilling playful behaviour, often related to an exaggerated conceit, easily translated into an excess of presence and an excess of virtuosity, a condition that is typical of the Web 2.0, a field full of skilful artisans who create an abundance of work that can easily be classified as Kitsch.